Application of plant metabolites to overcome antibiotic resistance of methicillin resistant Staphylococcus aureus (MRSA) - Santiago, Carolina (2015)
This study was designed to study the effects of ethyl acetate extracts from A. wilkesiana (9EA) and D. grandiflora (75EA-L and 75EA-B) and the respective bioactive fractions from these plants on methicillin resistance Staphylococcus aureus (MRSA ATCC 43300). A bioassay-guided isolation was used for fractionation of the crude extracts by combinations of liquid chromatography methods. The minimum inhibitory concentration (MIC) of crude extracts and fractions ranged between 12 to 0.75 mg/ml for MRSA and 6 to 0.75 mg/ml for methicillin sensitive S. aureus (MSSA ATCC 11630). The MIC values of beta-lactam antibiotics against MRSA strain (i.e. MIC of ampicillin = 50 µg/ml) used in this study were higher compared to MSSA (MIC of ampicillin = 6.25 µg/ml). The crude extracts and selected fractions were evaluated for synergistic activity with ampicillin. The kinetic growth curve experiment illustrated that combination of ampicillin and 9EA or 75EA-L or the fractions derived from these extracts (9EA-FC, 9EA-FD, FC-B, and 75EA-L) suppressed MRSA growth markedly. Results of fractional inhibitory concentration (FIC) index interpretation indicated synergism present in combination treatments of ampicillin and the plant test agents (FIC index < 0.05). Two fractions, FC-B and 75EA-L-F10 were identified to reduce MIC of ampicillin from 50 µg/ml to 1.56 µg/ml and 0.78 µg/ml respectively. These fractions were found to inhibit PBP2a production either alone or in combination with ampicillin in Western blot assay which offered a plausible explanation for restoration of ampicillin’s activity in combination treatment. The same fractions were investigated in MRSA biofilm study. Results showed that FC-B or 75EA-L-F10 alone inhibited MRSA biofilm production (~70-80% inhibition). Findings from microtiter attachment assay suggested that these fractions prevent cell-surface attachment (more than 90% inhibition) which is the initial step in biofilm formation. Whereas the PBP2a latex agglutination showed occurrence of low level of PBP2a in MRSA biofilm treated with FC-B or 75EA-L-F10 implicating possible disruption of cell-cell interactions required for microcolonies development. Ampicillin on the other hand has an inferior activity in preventing cell-surface attachment (37.8% inhibition) although it managed to inhibit MRSA biofilm production by 84.5%. A high performance liquid chromatography (HPLC) and phytochemical analysis showed the studied extracts and fractions are complex mixtures of plant metabolites belonging to the class of tannins, saponins, alkaloids, flavonoids, sterols/steroids, and glycosides. The resistance modifying properties and the anti-biofilm action found in this study are attributed to presence of these phytochemicals. Therefore, we propose that metabolites occurring in A. wilkesiana and D. grandiflora may be good candidates for development of new treatment for MRSA or as an adjuvant for the current antibiotics.